2007
DOI: 10.1021/jo070575f
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Aerobic Oxidation of α-Hydroxy Acid Derivatives by C4-Symmetric, Vanadate-Centered, Tetrakisvanadyl(V) Clusters Derived from N-Salicylidene-α-aminocarboxylates

Abstract: A series of chiral vanadyl(V) methoxides bearing 3-t-butyl-5-substituted N-salicylene-L-valinate and L-t-leucinate as chiral auxiliaries has been prepared. In all cases except the 3,5-di-t-butyl analogue, they exist as monomers both in solution and in the single crystal state. In the case of the 3,5-di-t-butyl analogue, the architectural nature of the vanadyl(V) complex highly depends on the base used during the complex formation event. A pentanuclear C4-symmetric complex was formed when potassium salts were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
20
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(23 citation statements)
references
References 48 publications
3
20
0
Order By: Relevance
“…This new protocol was particularly efficient when applied to α‐aryl‐α‐hydroxy esters and essentially all kinds of α‐hydroxy amides. Excellent selectivity factors of up to 500 were also obtained by these authors for the KR of a range of other α‐hydroxy acid derivatives including α‐hydroxy thioesters by using catalyst 35 82. It must be concluded from these studies that the best enantioselectivities were obtained through judicious selections of the C‐3 and C‐5 substituents in the N ‐salicylidene template of the catalysts employed.…”
Section: Kinetic Resolution Of Alcoholsmentioning
confidence: 81%
“…This new protocol was particularly efficient when applied to α‐aryl‐α‐hydroxy esters and essentially all kinds of α‐hydroxy amides. Excellent selectivity factors of up to 500 were also obtained by these authors for the KR of a range of other α‐hydroxy acid derivatives including α‐hydroxy thioesters by using catalyst 35 82. It must be concluded from these studies that the best enantioselectivities were obtained through judicious selections of the C‐3 and C‐5 substituents in the N ‐salicylidene template of the catalysts employed.…”
Section: Kinetic Resolution Of Alcoholsmentioning
confidence: 81%
“…Traditionally, α‐ketothioesters were obtained by means of the hydrolysis of trimethyl α‐oxo trithioorthoesters, the aerobic oxidation of α‐hydroxythioesters, and the hydrolysis of β‐keto α, α‐dichloro sulfides. [2a], These classic procedures mentioned above still suffer from some apparent drawbacks, such as the use of the flammable reagent ( tert ‐butyllithium) and the demand of expensive metal reagents. The reactions involving metal reagents usually are heterogeneous and produce a large amount of residue, which may restrict their application in industry.…”
Section: Introductionmentioning
confidence: 99%
“…The glyoxylamides are compounds of widespread interest in organic chemistry and present in many biologically active compounds [1][2][3][4][5][6][7][8]. In parallel with the application of the glyoxylamide in medicinal chemistry, numerous synthetic methods have been described in the literature [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. Other authors have also reported that synthesis of the glyoxylamide fragment could be achieved by the ring opening of Nacetylisatin 1 by attacking an amine at C2-carbonyl group of N-acetylisatin (Scheme 1) [27][28][29][30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%